Biotransformation of benzyl acetone using saccharomyces cerevisiae, aspergillus niger, pseudomonas aeruginosa, enterococcus faecalis and bacillus cereus - Norul Amalina, Sabri (2017)
Benzyl acetone, a carboxylic derivative constitute a considerable percentage of the overall yield of essential oil extracted from Aquilaria malaccensis (agarwood) and thus, considered as one of the major constituents of agarwood oil. This study aimed at isolating benzyl acetone from essential oil of A. malaccensis using preparative GC (prep-GC); studying the fate of benzyl acetone when transformed using selected microorganisms commonly found in environment; developing efficient biotransformation system by optimizing parameters namely initial substrate and glucose concentration, initial pH and temperature of reaction. Essential oil of A. malaccensis was extracted using Microwave-Assisted Extraction (MAE) and preparative GC (prep-GC) was used to isolate benzyl acetone. Identity of isolated benzyl acetone was confirmed by comparing the peak to that of commercial benzyl acetone using GC-MS. The whole cells of Saccharomyces cerevisiae, Aspergillus niger, Pseudomonas aeruginosa, Enterococcusfaecalis and Bacillus cereus were used for biotransformation of commercial benzyl acetone in this study. GC-MS was used to identify and quantify biotransformation product. Reduction of benzyl acetone to 4-phenyl-2-butanol occurred in all experiments using these five microorganisms. The optimum condition for the highest biotransformation activity using S. cerevisiae: 34.01 % conversion in 0.1 g/L benzyl acetone, 20 g/L glucose, pH 7.5 and 30°C; A. niger: 94.33 % conversion in 0.15 g/L benzyl acetone, 50 g/L glucose, pH 7.5 and 27°C; P. aeruginosa: 98.27 % conversion in 0.1 g/L benzyl acetone, 20 g/L glucose, pH 7.0 and 30°C; E.faecalis: 7.17 % conversion in 0.15 g/L benzyl acetone, 40 g/L glucose, pH 7.0 and 37°C; B. cereus: 9.84 % conversion in 0.15 gIL, 40 g/L glucose, pH 7.0 and 40°C. Biotransformation of benzyl acetone resulted in formation of 4-phenyl-2-butanol which is not naturally found in agarwood oil. P. aeruginosa was proven to be the most efficient biocatalyst for biotransformation of benzyl acetone to 4-phenyl-2-butanol, followed by A. niger, S. cerevisiae, E. faecalis and B. cereus.